High Level of Uterine Endocervical Interleukin-8, Matrix Metalloproteinase-8, and Interleukin 1Β as a Risk Factor for Preterm Labor - Suwardewa TGA; Suwiyoga K K; Mantik Astawa N; Sutirta Yasa IWP (Journal of Global Pharma Technology, 2017)
The preterm birth is a birth that takes place on a gestational age between 20–36 weeks and six days. The preterm birth   is the leading cause of neonatal mortality and morbidity. Despite the current treatment procedures, the incidence of preterm birth has not changed in the last two decades. Incomplete understanding of the pathophysiological mechanisms underlying preterm labor is the major obstacle to prevent preterm birth. Recently, endocervical inflammation has been thought as a risk factor of a preterm labor. Several important substances such as endocervical IL-8, MMP-8, and IL-1β, has been considered to play a key role on preterm birth through cervical ripening. With those assumptions, the detection of a higher level of uterine endocervical IL-8, MMP-8, and IL-1β can be used to predict preterm labor. The design of this study is an observational case control study with a case group, which consisted of pregnant women with 20–36 weeks and six days of gestational age who had signs of labor, and the control group consisted of pregnant women with 20–36 weeks and six days of gestational age who had no signs of labor. The material used for this study is cervical mucous, and the enzyme-linked immunosorbent assay method was used to assess the level of IL-8, MMP-8, and IL-1β at laboratory of Veterinary Medicine of Udayana University Denpasar. In this study we used 48 samples, among which 24 were case group, and 24 as a control group. The mean age of the women, gestational age, and parity from both group are (27.04 vs 28.62 years old), (31.8 vs 29.50 weeks), and (0.96 vs 1.29) respectively, which are statistically homogenous (p > 0.05). Each level of interleukin-8, matrix metalloproteinase, and interleukin-1β suggests a risk factor of a preterm labor for: 35 times (OR = 35.00; CI 95% = 6.95–176.39; p = 0.001); 6.6 times (OR = 6.60; CI 95% = 1.25–34.95; p = 0.016), and 8.3 times (OR = 8.3; CI 95% = 2.15–32.3; p = 0.001), orderly. Among these cytokines, one that contributes most through a preterm birth is interleukin-8 (61%), followed by matrix metalloproteinase-8 (27%), and interleukin-1β (12%).Conclusion: Endocervical inflammation with high level of IL-8, MMP-8, and IL-1β is a risk factor for preterm labor. IL -8 gives the most contribution on preterm labor.Keywords: Preterm birth, Endocervical IL-8, MMP-8, and IL-1β.